How does split announcement affect stock liquidity? Evidence from Bursa Malaysia - S. Amir Tabibian; Zhaoyong Zhang; Mohsen Jafarian (Risks, 2020)
This study examines the impact of stock splits on stock liquidity in Bursa Malaysia from 2004-2018. The study uses event study methodology and investigates liquidity changes, the role of liquidity, and the relationship between abnormal returns and liquidity as well. We found a significant liquidity improvement on the splits announcement, announcement of book closing date and split execution date (Ex-date), while it declined after the split Ex-date. The findings also indicate that firms with a low-level liquidity prior to split announcements experienced an increase in liquidity after Ex-date. Using panel data analysis, we find that the fixed effect model is more appropriate than the pooled OLS, and the abnormal announcement returns are driven by stock liquidity.
Keywords: 330; split announcement; stock liquidity; stock return; Bursa Malaysia